Studi Fenomenologi: Implementasi Moderasi Beragama pada Sekolah Ramah Anak di Kota Langsa - Husna, Khairul (Diksi: Jurnal Pendidikan dan Literasi, 2023)
This research aims to analyze the implementation of religious moderation in the context of Child-Friendly Schools. The concept of religious moderation is integrated as a foundation for creating an inclusive environment in schools, where religious differences are valued and supported. A qualitative approach with a phenomenological study design was used to explore the experiences of principals and teachers from MI Tahfidz Nur Shadrina Kota Langsa who were involved in this implementation. Data were collected through in-depth interviews. The results showed that religious moderation can be identified through indicators such as tolerance, integration of religious values, interfaith dialogue, and active participation of the entire school community. The findings provide insights into the effectiveness of religious moderation in creating an educational environment that supports religious diversity, contributes to the diversity education literature, and provides practical directions for schools that want to adopt a similar approach